A Comprehensive Bibliometric Analysis of School-Based Physical Activity Research - Dofredo, Kyla H.; Pinlac, Jelene T.; Pineda, Kylah R.; Gatus, Lovely L.; Briñas, Norlito Nickson N.; Miranda, John Paul P.; Tolentino, Julius Ceazar G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Physical activity has captured considerable interest from international academic scholars due to its fundamental role in maintaining optimal health. Thus, this study sought to examine the scholarly articles on school-based physical activity, employing a comprehensive bibliometric analysis extracted from the Scopus database spanning 2013 to 2023. A filtering protocol was utilized to guide the selection of articles, and analyses were facilitated solely by Python programming. This research yielded extensive insights encompassing document type, publication rates, citation rates, prevalent keywords, and geographic distribution. The results revealed the prominence of "Articles" as the primary document category. Notably, the year 2020 was observed as the highest publication count, with 2014 being the peak year for citation rates. However, both publication and citation patterns exhibited substantial fluctuations. These analyses collectively identify the United States as the largest contributor among the top ten countries, accompanied by substantial contributions from European nations. The analysis of the top 50 most-cited journal articles indicates a prevalence of articles authored by one to five individuals, with a peak in publications during 2014, followed by a gradual decline. Notably, the keyword "children" prominently emerges across the datasets, underscoring its frequent utilization in the context of school-based physical activity research.